INTERPERSONAL METAFUNCTION IN BIRTHDAY AND CONDOLENCE MESSAGES: A COMPARATIVE REGISTER ANALYSIS OF DIGITAL DISCOURSE - Sanka Washew; Daniel Dwamena Ofosu; Andrews Kwame Osei (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study applies Halliday’s Systemic Functional Linguistics (SFL) to compare interpersonal meanings in birthday and condolence messages. The study focuses on mood, modality, and pronoun use to examine how language constructs and sustains social relationships in celebratory versus grief contexts. A descriptive qualitative research design was used to gather and analyse data, consisting of 250 birthdays and 250 condolences messages from online message sources. Data were annotated with the UAM Corpus Tool, 6.2, to identify the interpersonal features of the texts. Results indicate that both registers are dominated by a declarative mood, but they differ in orientation. Birthday messages emphasised positive affect through certainty, possibility, and intention, while condolence messages use greater syntactic complexity, deontic modality, and third-person pronouns to acknowledge loss and express sympathy. The study advances an SFL-based register of short-form digital discourse and reveals how linguistic choices encode empathy, solidarity, and emotional alignments in contextually contrasting, yet relationally intimate genres. This study contributes to register analysis in digital discourse by highlighting interpersonal metafunctions in contrasting genres.